Earnings mobility in Argentina, Mexico, and Venezuela: testing the divergence of earnings and the symmetry of mobility hypotheses - Gary S. Fields; Robert Duval-Hernández; Samuel Freije; María Laura Sánchez Puerta (Institute for the Study of Labor (IZA), 2007)
This paper examines changes in individual earnings during positive and negative growth periods in three Latin American economies: Argentina, Mexico, and Venezuela. We ask whether those individuals who start in the best economic position are those who experience the largest earnings gains or the smallest earnings losses; this is the divergent, mobility hypothesis. We also compare periods of positive economic growth with those of negative economic growth, asking whether those groups of individuals that experience large positive earnings gains when the economy is growing are the same as those that experience large earnings losses when the economy is contracting; this is the symmetry of mobility hypothesis. We find very occasional support for the divergent mobility hypothesis in scattered years in the cases of Mexico and Venezuela, and no support at all in the case of Argentina. Rather, earnings mobility is most frequently convergent or neutral in all three countries. As for the symmetry of mobility hypothesis, we find that it is rejected in most cases; rather, those groups that gain the most when the economy is growing are also the ones that gain the most when the economy is contracting. Furthermore, we explain how the absence of divergence is compatible with rising inequality in the countries under study.
Keywords: D31; 330; Earnings mobility; income convergence; Latin America; Soziale Mobilität; Wirtschaftswachstum; Einkommensverteilung; Vergleich; Argentinien; Mexiko; Venezuela